In silico study of Andrographolide from Andrographis paniculata (Burm F.) Ness as an anti-colorectal cancer agent - Viranti, Milfa; Baroroh, Umi; Astriany, Dewi (Jurnal Penelitian, 2024)
Cancer is one of the leading causes of death in the world, one of which is colorectal cancer, a malignant tumor in the epithelial tissue of the colon and rectum. Cancer treatment is long-term, so it has an impact on physical and psychological changes for patients. There was many exploration of anticancer drug candidates from natural ingredients such as andrographolide compounds. The in silico method can be done to predicts the absorption, distribution, metabolism, and excretion (ADME) of andrographolide compounds and meets Lipinski Rule of Five. The toxicity of andrographolide compounds was classified in class 4, which needs dose supervision. The prediction of activity potential is quite good based on the Structure-Activity Relationship (SAR). The results of molecular tethering of the three target receptors, namely Cyclooxigenase-2 (COX-2), caspase-3, and Vascular Endothelial Growth Factor Receptor-2 (VEGFR-2), showed that caspase-3 has the best binding value or affinity of -5.36 kcal/mol, with quite a lot of hydrogen bonds of 7. The amino acids formed in andrographolide compounds are the same as the baseline ligands, so it can be concluded that andrographolide has colorectal anticancer activity and can increase caspase-3 activity in colorectal cancer cells.